Migrations in the Mediterranean Between Protection of Human Rights and Border Control. An Italian Perspective - Cataldi, Giuseppe (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
Migration through the Mediterranean has to be considered nowadays no more as an emergency. The first urgency is always to save lives at sea, and the Italian Mare Nostrum Operation has been a good example, not followed by EU choices. At the moment border surveillance and the fight against trafficking and smuggling of migrants seem to be the priorities in EU policy and action. The EU Dublin System is now facing a huge crisis and the new models, in particular the Statement agreed with Turkey, do not convince from a legal point of view, mainly because refugees deserve a special attention, based on the non-refoulement principle. The time has come to exit the logic of emergency and formulate a lasting policy to manage migrations, implementing Lisbon Treaty and CFR principles based on solidarity and respect of human rights, as well as on true cooperation among States.